DIPLOMASI INDONESIA KEPADA ARAB SAUDI DALAM PENAMBAHAN KUOTA IBADAH HAJI PERIODE 2017-2020 - Sita Sabrina (2021)
This research aims to describe the efforts of the Indonesian government in increasing the hajj quota in Indonesia so as to reduce the length of waiting list of hajj in Indonesia. This research uses qualitative research methods and its supported by the theory of multi-track diplomacy, national interests and organizing the hajj pilgrimage in Indonesia in assessing the title of this research. Because Indonesia is a country with the largest Muslim population in the world and Hajj is one of the fifth pillars of Islam. The problem of Hajj in Indonesia which is the concern of many parties is the limitation of Hajj quota for Indonesia causing a prolonged waiting list. The number of Indonesian Muslims who want to perform the pilgrimage is not comparable to the quota given by the Saudi Arabian government. Diplomatic efforts carried out by the Indonesian government succeeded in increasing the Hajj quota, which was to get an additional quota of 10,000 in 2019.